2021
DOI: 10.1016/j.aninu.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species regulate porcine embryo development during pre-implantation period: A mini-review

Abstract: Significant porcine embryonic loss occurs during conceptus morphological elongation and attachment from d 10 to 20 of pregnancy, which directly decreases the reproductive efficiency of sows. A successful establishment of pregnancy mainly depends on the endometrium receptivity, embryo quality, and utero-placental microenvironment, which requires complex cross-talk between the conceptus and uterus. The understanding of the molecular mechanism regulating the uterine-conceptus communication during porcine conceptus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Rapid fetal growth during pregnancy leads to increased metabolic burdens on pregnant women or dams, causing elevated systemic oxidative stress [ 1 , 2 ]. Accumulating evidence suggests that maternal oxidative stress is associated with the occurrence of adverse pregnancy outcomes, such as preterm birth, preeclampsia, low birth weight, and fetal death [ 3 , 4 ]. The placenta is the only site for the transfer of nutrients to the fetus during gestation; thus, the placenta’s health and function are closely associated with the development of a healthy fetus [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid fetal growth during pregnancy leads to increased metabolic burdens on pregnant women or dams, causing elevated systemic oxidative stress [ 1 , 2 ]. Accumulating evidence suggests that maternal oxidative stress is associated with the occurrence of adverse pregnancy outcomes, such as preterm birth, preeclampsia, low birth weight, and fetal death [ 3 , 4 ]. The placenta is the only site for the transfer of nutrients to the fetus during gestation; thus, the placenta’s health and function are closely associated with the development of a healthy fetus [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The endometrial cells which line the uterus play a crucial role in fertilization and implantation, while during menstruation and pregnancy they produce ROS. It has been demonstrated that endometrial cell production of H 2 O 2 and O 2 during the menstrual cycle contributes to the control of endometrial receptivity and implantation [ 16 , 17 ].…”
Section: Ros In the Female Reproductive Systemmentioning
confidence: 99%
“…During pregnancy, especially during late gestation, sows are experiencing progressive oxidative stress because of the significant increase in the fetal and mammary gland growth rates [ 1 , 2 , 3 ], accompanied by a decrease in antioxidant enzymes in the sows’ blood [ 4 ]. Accumulating evidence indicates that maternal oxidative stress is associated with the occurrence of poor pregnancy outcomes, such as fetal death, preeclampsia, preterm birth, and intrauterine growth restriction (IUGR) [ 5 , 6 ]. Thus, relieving maternal oxidative stress during late pregnancy can be an effective strategy to improve sow reproductive performance.…”
Section: Introductionmentioning
confidence: 99%